The Effect of Bromocriptine Injection on Ovarieres and Uteri Through Early Pregnant Stages in Albino Mice - AL- Janabi, A. S .; Taha, M. N .; AL – Abbodi, A. A . Z. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study was carried out on 10 adult females of albino mice ,  aged  8 â€“ 10 weeks and      24 â€“ 27 gm weight . In addition to 10 males were used for mating in order to determine the effect of injection of bromocriptine on the early stages of pregnancy and this was observed by measuring the weights of some component of female  reproduction  .                                                    The animals were divided into groups : the first group as the control which were injected subcutaneously with normal saline , while the second group as the treated which were injected subcutaneously with 0.5 mg of bromocriptine throughout the time of the expermint ( 5 days ).            The results showed that there was a significant decrease ( P < 0.05 ) in consumpation of food and boody weight before killing , and also in weights of overies and uteri of treated animals in comparison with control . The result also showed the influence of bromocriptine in inhibiting the levels of prolactin hormone and the appearance of its negative effect on the earlier stages of pregnancy in mice through effect on the ovaries and uteri of these animals .